Pemanfaatan Air Kelapa dan Tepung Tapioka sebagai Bahan Baku Pembuatan Kertas Ramah Lingkungan dengan Aktivator Acetobacter Xylinum - Safida, Qadrun Hanan; Harunsyah, Harunsyah; Nahar, Nahar (Politeknik Negeri Lhokseumawe, 2025)
The use of cellulose derived from wood is increasing every year in Indonesia. This causes environmental damage that occurs continuously. In this research, paper making was carried out using coconut water and tapioca flour as raw materials as well as bacterial cellulose activator so that it is more environmentally friendly. The aim of this research is to determine the effect of variations in the mass of microbial cellulose and tapioca flour on the paper produced. The variables used in this research were the mass of microbial cellulose of 70, 75, 80, 85 90, 85 and 90 grams with variations in tapioca flour adhesive of 10, 15, 20, 25 and 30 grams. Next, the resulting paper is subjected to a grammage test, tensile strength test, water content test, functional group test (FTIR) and SEM test. In the grammage test, variations in the mass of microbial cellulose of 90 grams with a mass of tapioca flour of 30 grams had a higher grammage value than the others, namely 460 g/m2. In the tensile strength test, the highest value was in the variation of microbial cellulose mass of 80 grams with a mass of 10 grams of tapioca flour with a value of 0.930522 MPa, while in the water content test the highest value was in the variation of microbial cellulose mass of 90 grams with a mass of 30 grams of tapioca starch with a value of 17.42%.